A Meeting at Grandma's Camp (Selections) - Dufresne, Lucie Marie-Mai (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2026)
This excerpt from a longer paper presents a detailed description of a 1998 ‘supper tour’ to Atsua Ku, a First Nations fish camp on the Yukon River. This first-person narrative by the late Dr. Lucie Dufresne explores the negotiated identities and relationships of the inhabitants and owners of the fish camp with herself as the lone tourist to visit that day.